La lectura crítica en la enseñanza aprendizaje de los niños/as de 3ro, 4to, 5to, 6to, y 7mo año de educación general básica de la escuela Daniel Evas Guaraca” de la comunidad Atapo Quillotoro, parroquia Palmira, cantón Guamote, provincia de Chimborazo, año lectivo 2010-2011. - Chucuri Sagñay, Margarita (2011)
This research was conducted under the theme "Critical reading in the learning of children in 3rd, 4th, 5th, 6th, and 7th year of basic general education school "Daniel Eves Guaraca" of Quillotoro Atapo parish community Palmyra, Canton Guamote, Chimborazo Province, in 2010-2011. In the majority of students in 3rd, 4th, 5th, 6th, and 7th year of general basic education has been that children have difficulty in the process of critical reading, a situation which leads us to obtain real data for analysis on the problems presented. The theoretical framework contributes to theories of critical reading and active techniques necessary for effective teaching and learning with children, has obtained information from bibliographic sources and different authors, properly orienting the knowledge necessary to help children and children with special learning problems of critical reading. In order to test hypotheses related to the subject of study and reach conclusions and recommendations, carried out an analysis of all information collected through the instruments, which shows that children in the 3rd, 4th, 5th, 6th, and 7th year of elementary schools of the school, "Daniel Eves Guaraca", presents some difficulties in the teaching-learning process of critical reading. The study required the use of methods: descriptive and field techniques with today's students critical reading of the 3rd, 4th, 5th, 6th, and 7th year of basic education can make a smooth short, they can understand what read and make constructive criticism of the theme.